ANO7 in aggressive prostate cancer - Kaikkonen, Elina (fi=Turun yliopisto|en=University of Turku|, 2020)
A significant proportion of men develop prostate cancer during their lifetime, which causes challenges for public health. PSA screening studies have shown that testing all men at specific ages causes overdiagnosis of prostate cancer and unnecessary treatments for individuals who have indolent disease. Additional methods are required alongside PSA testing to be able to prognosticate the disease outcome and to focus the treatments on aggressive prostate cancer cases. The chromosomal location 2q37.3, where the transmembrane protein coding gene Anoctamin 7 (ANO7) resides, is associated with prostate cancer susceptibility in linkage analyses and genome-wide association studies (GWAS). In addition, ANO7 has been considered to be expressed specifically in prostate tissue, and it has been suggested as a target for prostate cancer immunotherapy. This thesis work concentrates on investigating the role of ANO7 in prostate cancer. ANO7 expression was significantly higher in prostate tissue than in any other tissue type, and ANO7 expression was elevated in prostate cancer compared to benign tissue. Moreover, elevated expression was associated with poor survival among patients. Next-generation sequencing (NGS) analysis of the ANO7 gene revealed possible truncating rare germline variants, which were found only in prostate cancer patients and not in controls in the initial screening. These variants were genotyped from several different prostate cancer patient cohorts and sets of unaffected males. The stop-gain variant in exon 1 was associated with poor survival, and the variant in intron/exon 4 was associated with aggressive disease. Because the intron/exon 4 variant was related to aggressive cancer but not to poor survival, we investigated whether the variant carriers would have a good response to docetaxel treatment in castration-resistant prostate cancer. As was hypothesized, the variant carriers had a better response to docetaxel than the non-carriers. When investigating ANO7 protein interactions, we observed an enrichment specifically in proteins related to vesicle trafficking. This study indicates that ANO7 has a role in prostate cancer development and that truncating mutations in the gene predispose patients to aggressive prostate cancer. The variants reported in this study could facilitate precision medicine for prostate cancer patient care.

ANO7 aggressiivisessa eturauhassyövässä Eturauhassyöpä on kansanterveydellinen haaste, koska suuri osa miehistä saa taudin vanhetessaan. PSA-seulontatutkimukset ovat osoittaneet, että kaikkien tietyn ikäluokan miesten testaaminen aiheuttaa ylidiagnosointia ja turhia hoitoja niille, joiden syöpä ei etene aggressiiviseksi. Sen lisäksi, että eturauhassyövän hoidosta aiheutuvat kustannukset terveydenhuoltojärjestelmälle ovat suuret, ylidiagnosointi aiheuttaa haittaa ja huolta myös potilaalle itselleen. PSA-testauksen rinnalle tarvitaankin muita menetelmiä, joiden avulla potilaiden taudin ennustetta voitaisiin paremmin määrittää. Kromosomaalinen alue 2q37.3, jossa solumembraaniproteiinia koodaava Anoktamiini 7 (ANO7) sijaitsee, on yhdistetty eturauhassyöpään genominlaajuisissa assosiaatioanalyyseissa (GWAS) ja kytkentäanalyyseissa. ANO7-geenin on ajateltu ilmentyvän spesifisesti eturauhasessa ja sitä on ehdotettu myös eturauhassyövän immunoterapian kohteeksi. Väitöskirjassa selvitettiin ANO7:n roolia eturauhassyövässä. Tutkimuksessa selvisi, että ANO7 ilmentyy enemmän eturauhasessa kuin muissa kudoksissa ja enemmän syövässä kuin normaalikudoksessa. Voimakas ilmentyminen oli lisäksi yhteydessä huonompaan eturauhassyövän ennusteeseen. ANO7-geenistä löytyi uuden sukupolven sekvensointimenetelmällä (NGS) proteiinille todennäköisesti haitallisia harvinaisia ituratavariantteja. Variantti ensimmäisessä eksonissa oli yhteydessä lyhentyneeseen elinaikaan ja intronialueella/eksonissa 4 oleva variantti assosioitui sairastumisriskiin ja aggressiiviseen tautiin. Koska intonin/eksonin 4 variantti oli yhteydessä aggressiiviseen tautiin, mutta ei lyhentyneeseen elinaikaan, tutkimme, hyötyvätkö variantin kantajat erityisen hyvin kastraatioresistentin syövän hoidossa käytettävästä docetaxel-lääkkeestä. Variantin kantajat saivat oletuksen mukaisesti paremman lääkevasteen. Kun tutkimme tarkemmin ANO7:n kanssa interaktoivia proteiineja, saimme selville, että solujen vesikkeliliikenteeseen osallistuvat proteiinit olivat yliedustettuina. Tämä tutkimus osoittaa, että ANO7 on osallisena eturauhassyövän kehityksessä ja proteiinille haitalliset variantit altistavat aggressiiviselle eturauhassyövälle. Tutkimuksessa löydettyjä variantteja voidaan mahdollisesti hyödyntää tulevaisuudessa eturauhassyövän yksilöllistetyssä hoidossa.